Implementation of Android Smartphone as CCTV Camera Based on Wifi Network - Herri Setiawan; Tasmi Tasmi; Husnawati Husnawati (Universitas Bina Darma, 2020)
The Security systems using cameras as monitors or what is commonly known as Closed Circuit Television (CCTV) have recently become more prevalent. However, to have a monitoring system or monitoring requires a fairly expensive cost to buy hardware and installation services. On the other hand, the development of mobile devices is increasingly being used, such as smartphones and tablets. The ease of carrying and the variety of applications available such as WIFI devices and a series of other applications and at relatively affordable prices have made this mobile device more and more in demand by the public today. This research is based on the idea of ​​creating a CCTV camera application using a smartphone that is always with us. This use will be useful for seeing the state of the room or certain places and can be monitored directly using the Android mobile device itself or from a Laptop / PC / Tablet and others.